2022
DOI: 10.4103/ua.ua_12_21
|View full text |Cite
|
Sign up to set email alerts
|

Isolated tuberculous orchitis presented as epididymo-orchitis: An unusual presentation of tuberculosis

Abstract: Urogenital tuberculosis (UGTB) is almost 8%–15% of the extrapulmonary site of TB of all kinds, and epididymal involvement is rarer, counted only 28% of UGTB. Isolated tuberculous epididymitis (ITE), without the inclusion of prostate or clinical evidence of renal involvement, is an even more rare entity and is challenging to diagnose. However, isolated epididymis TB presented as a huge scrotal abscess with scrotal sack involvement is exceptionally uncommon. The symptoms of such ITE resemble the epididymo-orchit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 30 publications
0
21
0
1
Order By: Relevance
“…A study conducted in a single teaching hospital in Ethiopia reported GUTB as the fourth most common form of EPTB, following lymph node, abdominal, and pleural involvement (8). Its involvement is rare, attributes for 8-15% of all EPTB cases (7,9). Concomitant active PTB or history of previous PTB might be evident in approximately 56-87% of patients (10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study conducted in a single teaching hospital in Ethiopia reported GUTB as the fourth most common form of EPTB, following lymph node, abdominal, and pleural involvement (8). Its involvement is rare, attributes for 8-15% of all EPTB cases (7,9). Concomitant active PTB or history of previous PTB might be evident in approximately 56-87% of patients (10).…”
Section: Discussionmentioning
confidence: 99%
“…Pathological examination and culture with isolation of mycobacteria are the gold standard con rmatory tests for TB diagnosis. The specimen to be tested was acquired either through ne-needle aspiration or biopsy ( FNAC/B), or through surgical biopsy (7). FNAC can provide a histological diagnosis when a clinical and radiological suspicion of malignancy is unlikely.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Juliana Garcia Alves da Trindade [1]  , Ana Caroline Siquara-de-Sousa [2]  and Diogo Goulart Corrêa [1] …”
Section: Testicular Tuberculosisunclassified